Improvement of whole-cell transamination with Saccharomyces cerevisiae using metabolic engineering and cell pre-adaptation. Issue 1 (December 2017) - Weber, Nora; Gorwa-Grauslund, Marie; Carlquist, Magnus
Abstract Background Whole-cell biocatalysis based on metabolically active baker's yeast with engineered transamination activity can be used to generate molecules carrying a chiral amine moiety. A prerequisite is though to express efficientω -transaminases and to reach sufficient intracellular precursor levels. Results Herein, the efficiency of three differentω -transaminases originating fromCapsicum chinense, Chromobacterium violaceum, andOchrobactrum anthropi was compared for whole-cell catalyzed kinetic resolution ofracemic 1-phenylethylamine to (R )-1-phenylethylamine. The gene from the most promising candidate, C .violaceum ω -transaminase (CV-TA), was expressed in a strain lacking pyruvate decarboxylase activity, which thereby accumulate the co-substrate pyruvate during glucose assimilation. However, the conversion increased only slightly under the applied reaction conditions. In parallel, the effect of increasing the intracellular pyridoxal-5′-phosphate (PLP) level by omission of thiamine during cultivation was investigated. It was found that without thiamine, PLP supplementation was redundant to keep high in vivo transamination activity. Furthermore, higher reaction rates were achieved using a strain containing several copies of CV-TA gene, highlighting the necessity to also increase the intracellular transaminase level. At last, this strain was also investigated for asymmetric whole-cell bioconversion of acetophenone to (S )-1-phenylethylamine usingl -alanine as amine donor. Although functionality could be demonstrated, the activity was extremely low indicating that the native co-product removal system was unable to drive the reaction towards the amine under the applied reaction conditions. Conclusions Altogether, our results demonstrate that (R )-1-phenylethylamine with >99%ee can be obtained via kinetic resolution at concentrations above 25 mMracemic substrate with glucose as sole co-substrate when combining appropriate genetic and process engineering approaches. Furthermore, the engineered yeast strain with highest transaminase activity was also shown to be operational as whole-cell catalyst for the production of (S )-1-phenylethylamine via asymmetric transamination of acetophenone, albeit with very low conversion.